2019
DOI: 10.1002/ece3.4999
|View full text |Cite
|
Sign up to set email alerts
|

Variable effects on growth and defense traits for plant ecotypic differentiation and phenotypic plasticity along elevation gradients

Abstract: Along ecological gradients, phenotypic differentiation can arise through natural selection on trait diversity and magnitude, and environment‐driven plastic changes. The magnitude of ecotypic differentiation versus phenotypic plasticity can vary depending on the traits under study. Using reciprocal transplant‐common gardens along steep elevation gradients, we evaluated patterns of ecotypic differentiation and phenotypic plasticity of several growth and defense‐related traits for two coexisting but unrelated pla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 119 publications
7
22
1
Order By: Relevance
“…The capacity of low altitude plants to increase production of TA-G and di-PIEs when grown under low altitude atmospheric pressure could benefit these plants and may be an adaptive trait, as latex metabolites have defensive functions against root feeders (Huber et al 2016a, b; Bont et al 2017) and herbivore pressure is often expected to increase with decreasing altitude (Rasmann et al 2014; Moreira et al 2018). These findings are consistent with previous studies showing that within species, constitutive defenses often decrease with increasing altitude (Bakhtiari et al 2019; Buckley et al . 2019; Meyer & Carlson 2001; Pellissier et al 2014).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The capacity of low altitude plants to increase production of TA-G and di-PIEs when grown under low altitude atmospheric pressure could benefit these plants and may be an adaptive trait, as latex metabolites have defensive functions against root feeders (Huber et al 2016a, b; Bont et al 2017) and herbivore pressure is often expected to increase with decreasing altitude (Rasmann et al 2014; Moreira et al 2018). These findings are consistent with previous studies showing that within species, constitutive defenses often decrease with increasing altitude (Bakhtiari et al 2019; Buckley et al . 2019; Meyer & Carlson 2001; Pellissier et al 2014).…”
Section: Discussionsupporting
confidence: 93%
“…With increasing altitude, mountain habitats impose different environmental demands on plants, including harsher abiotic conditions and a lower intensity of biotic interactions (Rasmann et al 2014; Buckley et al 2019; Midolo & Wellstein 2020). Several studies found evidence that the genetic variation of plant secondary metabolites is shaped by these environmental gradients (Bernal et al 2013; Moreira et al 2018; Bakhtiari et al 2019; Buckley et al 2019; Bont et al 2020). However, the role of decreasing atmospheric pressure at increasing altitudes in shaping the evolution and expression of plant secondary metabolites is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…We found that low-elevation ecotypes produced more constitutive levels of secondary chemicals, independent of elevation of the common garden. That total IGs and CPGs are genetically fixed within ecotypes is in line with previous observations on the same (Bakhtiari et al, 2019), or other systems (Buckley, Pashalidou, et al, 2019;Pellissier et al, 2012), which suggests that plant defences are associated with the covariation of both abiotic (climate) and biotic (local herbivore pressure) factors (Pellissier et al, 2012). Contrary to total production, chemical diversity appeared rather climate-dependent, in which case it was higher when plants were growing at the low-elevation common garden site.…”
Section: Plant Chemical Differences Related To Growth At Different supporting
confidence: 87%
“…Here we specifically aimed to measure the effect of climate and RAM communities on the ecotypic differences in both constitutive and inducible chemical defence phenotypes and plant growth, by performing a full-factorial reciprocal transplant experiment. We hypothesized that ecotypic functional trait differences between highand low-elevation sites, as previously observed (Bakhtiari, Formenti, Caggìa, Glauser, & Rasmann, 2019;Halbritter et al, 2018;Pellissier et al, 2014;Vitasse et al, 2009), are driven by both the variation in climatic factors and the differences in RAM communities. According to previous observations, we predicted that high-elevation climate (cold and humid) inhibits both defences and growth (Pellissier et al, 2014).…”
mentioning
confidence: 93%
“…Second, because most of the studied subalpine and alpine species are perennial, measuring traits in the field made it possible to target mature individual plants under natural conditions, as done in previous herbivory association studies (Descombes, Marchon, et al, 2017;Pellissier et al, 2013). This approach does not allow to entirely tease apart individual genotypes from their local environments in producing the observed phenotypes, possibly generating noise from the experiment design (Bakhtiari, Formenti, Caggìa, Glauser, & Rasmann, 2019;Woods, Hastings, Turley, Heard, & Agrawal, 2012). In the future, physical traits and chemical analyses could be compared in more controlled settings such as climate chambers (Pellissier et al, 2014).…”
Section: Limitationsmentioning
confidence: 99%